Akuntansi Keperilakuan Pada Akuntansi Sumber Daya Manusia dan Akuntansi Sosial - Risawati Risawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
In the rapidly evolving landscape of global business entites, organizational effectiveness plays an increasingly crucial role. The success or failure of an organization is heavily dependent on the quality of human resources, recognized as the most vital organizational assets. This research aims to measure human resource accounting and explore the concept of behavioral accounting in two critical contexts: human resource accounting (HRA) and social accounting. The research method employed is qualitative, focusing on past and current phenomena. Findings indicate that, from a conventional accounting perspective, human resources have not been fully recognized as assets. Human resource accounting is a novel concept in financial accounting, requiring further research. This understanding emphasizes that employees are considered organizational assets through a cost or human value approach. The implication is the need for integrating behavioral dimensions in human resource management and social aspects in accounting decision-making to enhance organizational effectiveness holistically. This research is expected to contribute to the development of behavioral accounting theory and practice, providing insights into the role of accounting in social and human resource contexts.